THE EFFECT OF THE TALKING STICK LEARNING MODEL ON THE LEARNING OUTCOMES OF CLASS IV STUDENTS IN THE SUBJECT OF MATHEMATICS MIXED ACCOUNTING OPERATIONS - Firdausi, Farihah; Nuriadin, Ishaq (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2024)
The aim of this research is to determine the effect of the Talking Stick learning model on learning outcomes for fourth-grade elementary school students. This research method uses a quantitative method with a quasi-experimental approach and a non-probability sampling technique. Researchers used pre-tests and post-tests to determine the development and impact of students' learning results by implementing the Talking Stick learning model. The data collection technique in this research uses hypothesis testing (t-test) to determine the effect of the talk stick collaborative learning model on critical mathematical thinking. This is reflected in the results of the hypothesis test (t-test) which has a significance value of 0.006 0.05. Therefore, it can be concluded that there is an influence on the learning outcomes of mixed arithmetic operations using the Talking Stick learning model.